Imiquimod triggering varicella zoster reactivation in an immunocompetent patient - Stewart, Thomas Jonathan; Tomizawa, Andrea; Rosen, Robert (International Journal of Basic & Clinical Pharmacology, 2017)
Imiquimod is widely used for the treatment of superficial basal cell carcinoma as well as several other dermatologic conditions. While its local immunostimulatory action is well proven, its potential for systemic immunomodulation has been less well described. We report the first case (to our knowledge) of varicella zoster reactivation caused by Imiquimod in an immunocompetent patient.